Structural Validity of ‘Santa Clara Strength of Religious Faith Questionnaire’ in Greek Sample - Dianni, Maria (Religions, 2014)
The aim of the present study was to investigate the structural validity and reliability of the Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ) instrument in the Greek population. One hundred and three individuals (men n = 45, and women n = 58) participated in this study. Their age ranged from 17 to 86 years. More specifically, the study investigated the fit of both versions of SCSRFQ (10-item and 5-item). The results of the present study revealed that both versions have adequate fit and can be used by Greek researchers as a measure of strength of religious faith in the Greek population.